(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Inguinal hernia repair is most frequently preformed surgeries by most of the general surgeons worldwide. Pain is the most common symptom post operative in both immediate and chronic phase. Pain management in these patients, especially in the immediate post operative time, is major concern for both patients and the medical fraternity.Material & Methods: A comparative study to evaluate the post operative pain in management of open inguinal hernia repair with and without inguinal nerve block was conducted at Dept. of General Surgery in Santosh Medical College and Hospital, Ghaziabad on patients admitted in Dept of General Surgery from September 2020 to August 2021. All patients underwent Lichtenstein tension free mesh repair for inguinal hernia. Half the patients randomly selected were given inguinal nerve block using 0.25% levobupivicaine.Results: Nerve blocks have been used for chronic pain managements in past in post op inguinal hernia repair surgeries. Present study deals with pain management in immediate post- operative pain management. It shows significant difference is noted in patients receiving the nerve block not only in pain but also comfort levels, post operative mobility, day of discharge and retention of urine.Conclusion: Use of nerve blocks in patients undergoing open inguinal hernia repair is beneficial for the patient with improved outcome.